Zur Struktur der Oxydationsprodukte aromatischer Aldoxime - B. Unterhalt; U. Pindur (CHIMIA)
By oxidizing aromatic aldoximes one may get products the structures of which are problematical. Using PMR-spectroscopy in testing the oxidized p-methyl- and p-isopropyl-benzaldoximes we could find their structures to be not symmetrical.